Estimation of palladium-103 radionuclide producibility at the cyclotron CV-28 for nuclear medicine - Petrusenko, Yu.T.; Lymar’, A.G.; Nikolaichuk, L.I.; Ponomarenko, T.A.; Tutubalin, A.I.; Shepelev, A.G. (Вопросы атомной науки и техники, 2009)
Consideration is given to the possibility of 103P d radionuclide production in nuclear reactions on protons and
deuterons at the cyclotron CV −28, for a subsequent use of the radionuclide in medicine, in particular, for brachytherapy.
Activity estimates of 103P d produced on both the internal and external targets of the cyclotron CV − 28 are
given. The energy transferred by the proton/deuteron beam to the target under irradiation is determined. Possible
ways of heat removal from the target substrate are considered. У роботi розглядується можливiсть здобуття радiонуклiда паладiй-103 на циклотронi CV-28 в реакцiях на протонах i дейтронах для використання його в медицинi, для брахiтерапiї зокрема. Приведено
розрахованi оцiнки активностей напрацьованого 103P d на внутрiшнiй i зовнiшнiй мiшенях циклотрона
CV-28. Визначена енергiя, яка передається пучком протонiв i дейтронiв мiшенi при опромiненнi. Обговорюється можливiсть вiдведення тепла вiд пiдкладки мiшеней. В работе рассматривается возможность получения радионуклида палладий-103 на циклотроне CV-28 в
реакциях на протонах и дейтронах для использования его в медицине, для брахитерапии в частности.
Приведены рассчитанные оценки активностей наработанного 103P d на внутренней и наружной мишенях циклотрона CV-28. Определена энергия, передаваемая пучком протонов и дейтронов мишени при
облучении. Обсуждается возможность отвода тепла от подложки мишеней.